A framework for digital transformation and business model innovation - Tonder, Chanté van (Array, 2020)
With the advent of the Fourth Industrial Revolution, businesses are adapting to the use of digitalisation which requires the digital transformation of their existing business models. However, there is limited empirical research on this phenomenon. The purpose of this study is twofold: (i) to develop a framework for businesses to digitally transform their business models and (ii) to examine literature in order to identify and analyse the constructs underlying the three concepts of Digitalisation, Digital Transformation and Business Model Innovation. The study is qualitative in nature and is based on a narrative review. Relevant articles were identified by using international bibliographic databases and scrutinised using thematic analysis. The findings reveal that the first two constructs require digital capabilities and a digital strategy. The third construct requires digital transformation in the realm of customer-centricity, resources, processes and profit. A set of propositions was formulated and the commonalities were mapped. Based upon this map, a conceptual framework was developed. The findings will assist in the development of future instruments that can guide businesses to digitally transform existing business model elements. This study aims to fill the gap on how business model innovation should be pursued through digital transformation by developing a conceptual framework.